The Impact of fairy tales on shaping gender concepts among secondary school students in Vietnam - Le Thi, Kim Ut (Technium Education and Humanities, 2025)
Fairy tales, as a genre of folklore, significantly influence the cognitive process and the formation of gender stereotypes among lower secondary school students in Vietnam. This study analyzes traditional fairy tales that reflect and reinforce gender stereotypes within the cultural context of East Asia and Vietnam, thereby assessing their impacts on gender perceptions among Vietnamese lower secondary students. Drawing on gender theory frameworks, the research focuses on examining Vietnamese fairy tales and conducting quantitative surveys alongside in-depth interviews with some lower secondary school teachers. The findings reveal that a substantial number of Vietnamese fairy tales contain gender bias, depicting male and female characters in “traditional” ways: females are often portrayed as weak and submissive, while males are strong and decisive. Exploratory Factor Analysis (EFA) and Structural Equation Modeling (SEM) indicate a correlation between exposure to gender-stereotyped fairy tales and biased gender perceptions among students. ANOVA tests also reveal significant differences based on gender and residential area. The study proposes implications for the education sector, publishers, parents, and other stakeholders regarding the selection, adaptation, and transmission of fairy tales to promote equitable, flexible, and humanistic gender perspectives among the younger generation.